Vernacular mapping: affect, virtuality, performance - Gerlach, JA (2012)
In diagramming the recent, global proliferation in quotidian cartographic technologies and practices, this thesis is concerned with the re-imagining of durable geographic motifs and refrains; those of maps and mappings. Conceptually, the thesis works to explore and interrogate the underplayed non-representational registers of cartography. Specifically, this entails unsettling the assumed ontological security of maps as representational artefacts, at the same time accentuating their affective and virtual vectors through an attentiveness to their spatial emergence and performance. In doing so, maps are rendered here not as mimetic, static grids of existence, but as intensive performances, productive of an unqualified geographic and political potential; that is to say, spaces of the virtual. Empirically, these conceptual concerns are worked through a series of fieldwork traces that animate and narrate a number of quite distinct yet resonant cartographic performances; namely geographic encounters with a counter-cartography group in North Carolina; a digital, open-source mapping organisation in both the UK and Peru and finally with two examples of an institutional cartography: Google and Ordnance Survey. Through these mappings, these fieldwork traces, what the thesis works towards is a micropolitical diagramming of contemporary cartographic practices, a diagramming that complicates deliberately the representational certitude of maps, but moreover, one that affirms the (im)material, anticipatory and minor geopolitics of mapping; a mapping of and for the everyday; a mapping of and for the vernacular.